Sperm morphology and testis histological changes in 12% high cholesterol diet administered rats following Tualang honey supplementation and diet modifications - Hasan, Sakiinah; Abdul Rahim, Roslina; Alias, Mohd Afzal; Muhammad, Siti Aeshah @ Naznin; Abdullah, Nor Zamzila; Abdul Razak, Redzuan Nul Hakim (Malaysian society of Pharmacology & Physiology (MSPP) - 34th Scientific Meeting 2021, Frontiers in Pharmacology, 2021)
Background: Hypercholesterolaemia is recognized as a factor associated with male infertility. However, currently, there is limited therapy available. Tualang honey (TH) is a type of Malaysian polyfloral wild honey produced by the rock bee (Apis dorsata) proven to exert both anti-inflammatory and anti-oxidative effects. Objective: This study aimed to determine the effects of TH coupled with diet modification on sperm morphology and testis histology of 12% high cholesterol diet (HCD) administered rats. Methodology: Fifteen rats were fed with HCD for 16 weeks. They were then divided into 3 groups. Group A rats were not treated and continued HCD as control. Group B rats were supplemented with TH (3.0g/kg) and continued HCD, while group C was given TH (3.0g/kg) but was changed to a normal diet for 4 weeks. Results: Compared to group A, group B, and C demonstrated significant improvement in both sperm morphology and Johnsen testicular scoring compared to group A (p<0.001). However, there are no significant changes in Johnsen testicular scoring between the groups. Conclusion: Diet modification in addition to TH supplementation may further improve male fertility in HCD rats as compared to TH alone. Based on our findings, there is a need to further explore the potential TH in improving male infertility associated with hypercholesterolaemia.